Shattered Not Cracked: The Effect of Women's Executive Leadership. (1st October 2016) - Jalalzai, Farida
ABSTRACT: Several countries where women gained prime ministerial or presidential offices at earlier points witnessed the rise of at least one additional woman leader subsequently. Such contexts coexist with others stalled at only one case. Most commonly, countries have yet to be governed by any women, let alone several. What explains these differing patterns? This article examines two dynamics to answer this question: first, women's attainment of executive positions worldwide and second, the influence previous women leaders exert on the rise of female successors. Institutional features appear most decisive in accounting for whether a country is led by a woman. These same institutional explanations facilitate multiple women executives as do systems with weak presidencies. In addition, democracy, gender parity, longer histories of women's suffrage, and politically fragile contexts more often coincide with shattered glass ceilings.